Aspek-Aspek Nilai Moral Dalam Novel Surat Kecil Untuk Tuhan Karya Agnes Davonar Dan Implikasinya Terhadap Pembelajaran - Syamsul Anwar Sefudin (Universitas Pancasakti Tegal, 2017)
This study aims to (1) describe aspects of moral values the main character in the novel Surat Kecil Untuk Tuhan by Agnes Davonar (2) describe the implications for learning. The source of data in this study was Surat Kecil Untuk Tuhan by Agnes Davonar thick 235 pages, published by Agnes Davonar Publisher in Jakarta. The form of the data in this study was in the form of snippets or excerpts of a sentence or a paragraph contained in the novel Surat Kecil Untuk Tuhan by Agnes Davonar related to the moral aspect. The method used in this research was descriptive analysis method to get an overview of the theme, the mandate, character and characterization, setting, plot, moral aspects in a literary work. The results showed that in the novel Surat Kecil Untuk Tuhan by Agnes Davonar containing moral aspects. Moral aspects in question were the value of the struggle, the value of education, religious values and the value of friendship. This novel had a positive impact on learning in high school because there were good moral values to be imparted to students